Reduction of seafood processing wastewater using technologies enhanced by swim–bed technology - Radhi Baker, Bakar; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Abdul Aziz, Hamidi (Springer Nature, 2020)
The increasing growth of the seafood processing industries considerably requires more industrial process activities and water consumption. It is estimated that approximately 10–40 m3 of wastewater is generated from those industries for processing one-tonne of raw materials. Due to limitations and regulations in natural resources utilization, a suitable and systematic wastewater treatment plant is very important to meet rigorous discharge standards. As a result of food waste biodegradability, the biological treatment and some extent of swim-bed technology, including a novel acryl-ﬁbre (bioﬁlm) material might be used effectively to meet the efﬂuent discharge criteria. This chapter aims to develop understanding on current problems and production of the seafood wastewater regarding treatment efﬁciency and methods of treatment.